LncRNA LUCAT1 offers protection against human coronary artery endothelial cellular oxidative stress injury through modulating hsa-miR-6776-5p/LRRC25 axis and activating autophagy flux - Yanjun Wang; Xin Zhang; Mengmeng Ren; Shu He; Hengjie Bie; Mengyang Duan; Zhiyuan Chen; Qiaowei Jia; Boyu Chi; Xiongkang Gan; Chengcheng Li; Yahong Fu; et al. (Journal of Translational Medicine)
Abstract Background Coronary artery disease (CAD) has become a dominant economic and health burden worldwide, and the role of autophagy in CAD requires further clarification. In this study, we comprehensively revealed the association between autophagy flux and CAD from multiple hierarchies. We explored autophagy-associated long noncoding RNA (lncRNA) and the mechanisms underlying oxidative stress-induced human coronary artery endothelial cells (HCAECs) injury. Methods (1) Autophagy-related proteins including LC3, p62, Beclin1, ATG5, and ATG7 were immunohistochemical stained in coronary specimens; (2) The levels and function of autophagy in the HCAEC oxidative stress model were evaluated using western blot (WB), transmission electron microscopy (TEM), and mRFP-GFP-LC3 adenovirus transfection experiments; (3) The competing endogenous RNA (ceRNA) network of lncRNA LUCAT1/hsa-miR-6776-5p/LRRC25 axis was constructed and validated; (4) The expression levels of above autophagy-related RNAs in peripheral blood mononuclear cells (PBMCs) were verified by qPCR, and their diagnostic performance was subsequently analyzed using receiver operating characteristic (ROC) analysis. Results (1) The expression of LC3, Beclin1, ATG5, and ATG7 demonstrated a consistent decline whereas p62 expression exhibited an opposite increase as atherosclerosis progressed; (2) Autophagy levels was significantly elevated in HCAECs under oxidative stress, while inhibition of the initial stage of autophagy with 3-MA exacerbated cellular damage; (3) The lncRNA LUCAT1/hsa-miR-6776-5p/LRRC25 axis was established through bioinformatic prediction and validated by dual-luciferase reporter assay, which resulted in a significant decrease in autophagy levels in HCAECs; (4) In total, p62, ATG7, lncRNA LUCAT1 and LRRC25 were validated as robust diagnostic biomarkers for CAD. Conclusions Our results delineated the dynamic disruption of the autophagy landscape during the progression of human coronary atherosclerosis and identified the lncRNA LUCAT1/hsa-miR-6776-5p/LRRC25 axis, uncovered through transcriptomic profiling, as a protective mechanism against endothelial cell injury through autophagy activation. Furthermore, we recognized p62, ATG7, lncRNA LUCAT1, and LRRC25 as dependable autophagy-related diagnostic biomarkers in circulating PBMCs, correlating with CAD severity. Collectively, Our findings furnish novel insights into the intricate autophagy landscape at various levels of coronary atherosclerosis and propose potential diagnostic biomarkers, and a theoretical foundation for managing CAD patients.